Pemberdayaan Kelompok Usaha Wanita Tani di Desa Juriya Kecamatan Bilato Kabupaten Gorontalo - Debi, Yuliyanti S.; Musa, Farid Th.; Latare, Sainudin (Dynamics of Rural Society Journal, 2023)
To increase the status and role of women economically, empowering women helps them become independent women and maximize their potential. Women's health, knowledge, and abilities will increase with the existence of women's empowerment programs. For women farmers, especially in rural areas, women farmer groups are a place to gather and respect women. However, there is a possibility that it is not ideal that the women of Juriya Village have a group of women farmers. They lack independence and are usually passive in society, as can be seen from their actions. The data needed for this study were collected through observation, interviews, and documentation. The goal is to make the problem clear. Based on the results of research conducted to empower women in agricultural business groups in Juriya Village, Bilato District, Gorontalo Regency. It was concluded that: First, community participation, especially women who are members of the empowerment program, is very good. It can be seen how enthusiastic they are in participating in the activities that have been given. Second, the participation and motivation of good members does not determine the success of an empowerment program activity. This is due to several inhibiting factors including: Internal problems between members and the treasurer, lack of training for women farming groups, and lack of business permits, this has an effect on product marketing.